Characterization and model updating of modal parameters of a riveted joints structure / Nor Azela Tormodi - Tormodi, Nor Azela (2018)
Thin metal sheets are widely used to fabricate various types of aircraft components because of the flexibility and easily to form any shapes. However, it is really difficult to keep the components permanently attached through the surface contact in the numerical model. Through this study, the simplified model of aircraft wing structure made from thin aluminium sheets was evaluated. This simplified model of wing structure consists of three different types of components which are a plate (skin), spar and rib. There are only five components included in this structure which consist of one plate, one spar and three ribs.